Challenges and opportunities in the islet transplantation microenvironment: a comprehensive summary of inflammatory cytokine, immune cells, and vascular endothelial cells - Chen, Qi-dong; Liu, Long; Zhao, Xiao-hong; Liang, Jun-bo; Li, Shao-wei (Frontiers in Immunology, 2023)
It is now understood that islet transplantation serves as a β-cell replacement therapy for type 1 diabetes. Many factors impact the survival of transplanted islets, especially those related to the microenvironment. This review explored microenvironmental components, including vascular endothelial cells, inflammatory cytokines, and immune cells, and their profound effects on post-islet transplantation survival rates. Furthermore, it revealed therapeutic strategies aimed at targeting these elements. Current evidence suggests that vascular endothelial cells are pivotal in facilitating vascularization and nutrient supply and establishing a new microcirculation network for transplanted islets. Consequently, preserving the functionality of vascular endothelial cells emerges as a crucial strategy to enhance the survival of islet transplantation. Release of cytokines will lead to activation of immune cells and production and release of further cytokines. While immune cells hold undeniable significance in regulating immune responses, their activation can result in rejection reactions. Thus, establishing immunological tolerance within the recipient’s body is essential for sustaining graft functionality. Indeed, future research endeavors should be directed toward developing precise strategies for modulating the microenvironment to achieve higher survival rates and more sustained transplantation outcomes. While acknowledging certain limitations inherent to this review, it provides valuable insights that can guide further exploration in the field of islet transplantation. In conclusion, the microenvironment plays a paramount role in islet transplantation. Importantly, we discuss novel perspectives that could lead to broader clinical applications and improved patient outcomes in islet transplantation.